2017
DOI: 10.1177/0271678x17708691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the gray and white matter energy budgets of human brain function

Abstract: The insatiable appetite for energy to support human brain function is mainly supplied by glucose oxidation (CMR). But how much energy is consumed for signaling and nonsignaling processes in gray/white matter is highly debated. We examined this issue by combining metabolic measurements of gray/white matter and a theoretical calculation of bottom-up energy budget using biophysical properties of neuronal/glial cells in conjunction with species-exclusive electrophysiological and morphological data. We calculated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
176
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(183 citation statements)
references
References 58 publications
7
176
0
Order By: Relevance
“…Additionally, brain metabolism can differ dramatically among circuits, cell‐types, and even individual cells according to their moment‐to‐moment energy demand. For instance, upon stimulation and firing of action potentials, neuronal metabolic burden increases several fold, mainly due to energy demands associated to synaptic transmission (Yu, Herman, Rothman, Agarwal, & Hyder, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, brain metabolism can differ dramatically among circuits, cell‐types, and even individual cells according to their moment‐to‐moment energy demand. For instance, upon stimulation and firing of action potentials, neuronal metabolic burden increases several fold, mainly due to energy demands associated to synaptic transmission (Yu, Herman, Rothman, Agarwal, & Hyder, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, positron emission tomography studies in humans have shown increases of ~50% in blood flow and glucose consumption, but only of ~5% in O 2 consumption (Fox et al, 1988); calibrated functional magnetic resonance imaging estimates a similar value for the increase in both blood flow and glucose metabolism (~45%), but a slightly larger ~16% increase in O 2 consumption (Davis, Kwong, Weisskoff, & Rosen, 1998). 2 When glycolysis runs faster than oxidative metabolism, the excess pyruvate and NADH production is managed by the temporary 1 Neurons firing at 1 Hz (a modest rate) in the gray matter of the human brain are calculated to increase their metabolic burden by ~2.7-fold, in order to support processes like restoring the ionic gradients across the cell membrane, neurotransmitter release, vesicle recycling and Ca 2+ management (Yu, Herman, Rothman, Agarwal, & Hyder, 2018). 2 Other studies in the smaller brains of rats (Hyder et al, 1997) found little discrepancy between glucose and oxygen consumption with stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Their costs however include the energy needed to build the connections during development, the energy needed to maintain their proper functioning, and the space they require. While gray matter consumes more energy than white matter [Yu et al, 2017], the metabolic demands of white matter are still significant. In gray matter, most energy is used for synaptic activity, whereas in white matter, most energy is used to operate the sodium and potassium pumps that maintain electrochemical gradients across the axon membrane [Yu et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…While gray matter consumes more energy than white matter [Yu et al, 2017], the metabolic demands of white matter are still significant. In gray matter, most energy is used for synaptic activity, whereas in white matter, most energy is used to operate the sodium and potassium pumps that maintain electrochemical gradients across the axon membrane [Yu et al, 2017]. These costs may place limits on the number of neuronal connections that the organism can metabolically support.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate estimation of the metabolic cost of action potential generation and propagation is important for the calculation of energy budgets for individual neurons as well as for the whole brain (Hofman, 1983;Attwell and Laughlin, 2001;Lennie, 2003;Henry, 2005;Alle et al, 2009;Carter and Bean, 2009;Herman et al, 2009;Hasenstaub et al, 2010;Sengupta et al, 2010;Belanger et al, 2011;Harris and Attwell, 2012;Howarth et al, 2012;Yu et al, 2012;Hyder et al, 2013b;Moujahid et al, 2014;Sanganahalli et al, 2016). These estimates reveal computational rules such as optimal trade-offs between metabolic constraints and neural coding (Laughlin, 2001;Laughlin and Sejnowski, 2003;Lennie, 2003;Moujahid et al, 2011;Sengupta et al, 2013) and improve the interpretation of functional magnetic resonance imaging data (Logothetis, 2008;Hyder et al, 2013a;Hyder et al, 2013b;Shulman et al, 2014;Magistretti and Allaman, 2015;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%